2018
DOI: 10.1002/1873-3468.13311
|View full text |Cite
|
Sign up to set email alerts
|

Time‐resolved interaction proteomics of the GIGANTEA protein under diurnal cycles in Arabidopsis

Abstract: The plant‐specific protein GIGANTEA (GI) controls many developmental and physiological processes, mediating rhythmic post‐translational regulation. GI physically binds several proteins implicated in the circadian clock, photoperiodic flowering, and abiotic stress responses. To understand GI's multifaceted function, we aimed to comprehensively and quantitatively identify potential interactors of GI in a time‐specific manner, using proteomics on Arabidopsis plants expressing epitope‐tagged GI. We detected previo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 97 publications
1
38
0
Order By: Relevance
“…This blue light responsive protein-protein interaction must be intrinsic to these proteins, with SbFFL likely serving as the photoreceptor, since this activity is apparent in yeast in the absence of other plant proteins. The Arabidopsis GI interactions with FKF1 and ZTL are blue light-dependent (Kim et al, 2007;Krahmer et al, 2018;Pudasaini et al, 2017;Sawa et al, 2007). The FKF1-GI complex occurs in the cytosol and the nucleus, while the ZTL-GI interaction is proposed to be exclusively in the cytosol (Kim et al, 2007;Park et al, 2013).…”
Section: Fluorescence Of Comparable Intensity or Pattern Did Not Occumentioning
confidence: 99%
“…This blue light responsive protein-protein interaction must be intrinsic to these proteins, with SbFFL likely serving as the photoreceptor, since this activity is apparent in yeast in the absence of other plant proteins. The Arabidopsis GI interactions with FKF1 and ZTL are blue light-dependent (Kim et al, 2007;Krahmer et al, 2018;Pudasaini et al, 2017;Sawa et al, 2007). The FKF1-GI complex occurs in the cytosol and the nucleus, while the ZTL-GI interaction is proposed to be exclusively in the cytosol (Kim et al, 2007;Park et al, 2013).…”
Section: Fluorescence Of Comparable Intensity or Pattern Did Not Occumentioning
confidence: 99%
“…Previously, it was shown that UBP12 and UBP13 associate with ZTL and GI in vivo 14,25 . To test whether UBP12 or UBP13 proteins interact with the members of the ZTL/GI protein complex we performed yeast two-hybrid assays.…”
Section: Resultsmentioning
confidence: 97%
“…We identified UBIQUITIN-SPECIFIC PROTEASE 12 and 13 (UBP12 and UBP13) as high-confidence ZTL-interacting proteins, which were shown previously to have an unspecified role in clock function 14,24 . UBP12 and UBP13 also interact with GI in IP-MS experiments 25 , suggesting that either the UBPs interact with ZTL and GI independently or that ZTL, GI, and the UBPs exist together in a complex. UBP12 and UBP13 are closely related deubiquitylating enzymes that can cleave lysine 48-linked mono- or poly-ubiquitin from substrates 24,26 , interestingly, a biochemical role opposite to that of ZTL.…”
Section: Introductionmentioning
confidence: 99%
“…Although a previous study describes that GI encodes a protein with six transmembrane domains [63], the biochemical functions of GI are not understood. In yeast, two hybrid experiments performed with the Arabidopsis GI protein show that the N-terminal domain interacts with FKF1 [81], while the complete protein shows interactions with the CYCLING DOF FACTOR6 and DELLA protein [82,83]. As the differences in protein structure found between PhGI1 and PhGI2 do not match well known domains we cannot understand their functional differences.…”
Section: Discussionmentioning
confidence: 99%